Lymphocytic esophagitis: An Australian (Queensland) case series of a newly recognized mimic of eosinophilic esophagitis. Issue 5 (15th April 2019) - Islam, Shamsul; Lee, Antonio; Lampe, Guy
Abstract : Background and Aim: Lymphocytic esophagitis (LoE) is a recently described upper gastrointestinal tract "disorder" diagnosis of which hinges on histology and is characterized by the excessive infiltration of lymphocytes in the peripapillary fields of the esophageal epithelium, with clinical manifestations similar to those of eosinophilic esophagitis (EoE). In this article, we aim to describe for the first time the clinico‐pathological characteristics of a large cohort of Australian (Queensland) cases of LoE. Methods: Histological data that fulfilled the criteria (predominant lymphocytic infiltration in the peripapillary fields, none or minimal neutrophils or eosinophils, and no infection) were collected between January 2014 and May 2016 from a number of major Queensland Public Hospital anatomical pathology laboratories. Patient presentations were subsequently examined to compile clinical and endoscopic correlates. Results: A total of 62 cases of LoE were identified. The median age was 55 years, with 59.6% of subjects being male. Major clinical manifestations included dysphagia (32), epigastric or abdominal pain (8), gastro‐esophageal reflux (8), association with Crohn's disease (8), and vomiting or diarrhea (6). Endoscopy was normal in 47% of cases; 47% had appearances similar to those of EoE. There were three cases with associated mild monilial esophagitis (6%). Conclusion: LoE is a relatively recently recognized condition of the esophagus with variable clinical and endoscopic findings. Diagnosis is based on characteristic histological features. Further investigation is needed to ascertain the etiopathology and natural history of the condition and to establish a safe and effective treatment regimen. Abstract : This article describes 62 Australian cases of lymphocytic esophagitis, which is histologically characterized by heavy mucosal infiltration with T‐lymphocytes and mucosal edema and clinically presents like eosinophilic esophagitis with dysphagia, chest, or abdominal pain. Treatment is empirical with PPI, swallowed steroids, and esophageal dilation in rare cases.